The Effect of Anastomosis Time on Outcome in Recipients of Kidneys Donated After Brain Death: A Cohort Study. Issue 11 (November 2015) - Heylen, L.; Naesens, M.; Jochmans, I.; Monbaliu, D.; Lerut, E.; Claes, K.; Heye, S.; Verhamme, P.; Coosemans, W.; Bammens, B.; Evenepoel, P.; Meijers, B.; et al.
<x xml:space="preserve">Abstract</x> Whether warm ischemia during the time to complete the vascular anastomoses determines renal allograft function has not been investigated systematically. We investigated the effect of anastomosis time on allograft outcome in 669 first, single kidney transplantations from brain‐dead donors. Anastomosis time independently increased the risk of delayed graft function (odds ratio per minute [OR] 1.05, 95% confidence interval [CI] 1.02–1.07, p < 0.001) and independently impaired allograft function after transplantation (p = 0.009, mixed‐models repeated‐measures analysis). In a subgroup of transplant recipients, protocol‐specified biopsies at 3 months (n = 186), 1 year (n = 189), and 2 years (n = 153) were blindly reviewed. Prolonged anastomosis time independently increased the risk of interstitial fibrosis and tubular atrophy on these protocol‐specified biopsies posttransplant (p < 0.001, generalized linear models). In conclusion, prolonged anastomosis time is not only detrimental for renal allograft outcome immediately after transplantation, also longer‐term allograft function and histology are affected by the duration of this warm ischemia.